Divine sayings = Mishkāt al-anwār : 101 ḥadīth qudsī - Ibn al-ʻArabī, 1165-1240 (Anqa Pub., 2004)
One of the most important and influential early collections of hadith qudsi, this book contains 101 sayings that are categorized into three sections. The first 40 sayings each have a full, unbroken chain of transmission that goes back to God through the medium of the Prophet Muhammad. The second category are sayings mostly taken from well-known written collections. The final section is drawn from similar books, with Ibn 'Arabi adding one extra, orally transmitted hadith. Providing a full introduction to the importance of this tradition in Ibn 'Arabi's writing, this scholarly volume also includes complete English and Arabic texts of the sayings, full chains of transmission, and information on the manuscript sources.